GAMBARAN PAPARAN IKLAN TERKAIT MINUMAN MANIS PADA KELOMPOK USIA DEWASA MUDA - Herviana Herviana; Citra Dewi Anggraini; Amalina Rizma; Dedy Siska (Jurnal Kesehatan, 2025)
Sugar sweetened beverages (SSBs) are drinks with added sugar. Highly consumption SSBs can lead to weight gain, type 2 diabetes mellitus, cardiovascular disease, and several types of cancer. One factor influencing sugar sweetened beverage consumption is exposure to mass media advertising. The purpose of this study was to determine the description of advertising exposure related to sugar sweetened beverages in young adults. The research method was observational with a cross-sectional design. The total sample in this study was 158 samples with the criteria of young adults (19-29 years) domiciled in the Riau Islands. Data collected were sources of information exposure obtained by respondents regarding sugar sweetened beverages, including print media, social media, television, and all media. The results showed that social media was the most dominant medium in conveying information about sugar sweetened beverages in the young adults group at 81.6%. Further research is recommended to explore the correlation between advertising exposure and levels of sugar sweetened beverages consumption in young adults. In addition, a digital-based nutritional literacy program is needed to improve the negative impacts of sugar sweetened beverage consumption.